Different Types of Progressive Wave Solutions via the 2D-Chiral Nonlinear Schrödinger Equation - Osman, M. S.; Baleanu, Dumitru; Tariq, Kalim Ul-Haq; Kaplan, Melike; Younis, Muhammad; Rizvi, Syed Tahir Raza (Frontiers in Physics, 2020)
A versatile integration gadget namely the protracted (or extended) Fan sub-equation (PFS-E) technique is devoted to retrieving a variety of solutions for different models in many fields of the sciences. This essay treatises the dynamics of progressive wave solutions via the 2D-chiral nonlinear Schrödinger (2D-CNLS) equation. The acquired solutions comprise of dark optical solitons, periodic solitons, singular dark (bright) solitons, and singular periodic solutions. By emulating the results gained in this work with other literature it can be noticed that the PFS-E method is an auspicious technique for finding solutions to other similar problems. Furthermore, it revealed some new types of solutions that will help us better understand the dynamic behaviors of the 2D-CNLS model.